The “State of the Art of the EU”, the French Presidency and a Forecast of Future Franco-German Cooperation - Ulrike Guérot (Romanian Journal of European Affairs, 2008)
The French Presidency has more or less dropped its initial agenda and has turned nearly exclusively to crisis management, forced by the need to address the three major crises the EU stumbled into in the course of the second half of 2008: the institutional crisis after the Irish on the Treaty of Lisbon, the breakout of the Russian-Georgian war and the subsequent EU relations with Russia and the financial crisis and its potentially recessionary consequences.